Collecting Shakespeare: the story of Henry and Emily Folger - Grant, Stephen H. (Johns Hopkins Univ. Press, 2014)
In Collecting Shakespeare, Stephen H. Grant recounts the American success story of Henry and Emily Folger of Brooklyn, a couple who were devoted to each other, in love with Shakespeare, and bitten by the collecting bug. Shortly after marrying in 1885, the Folgers started buying, cataloging, and storing all manner of items about Shakespeare and his era. Emily earned a master's degree in Shakespeare studies. The frugal couple worked passionately as a tight-knit team during the Gilded Age, financing their hobby with the fortune Henry earned as president of Standard Oil Company of New York, where he was a trusted associate of John D. Rockefeller Sr. While a number of American universities offered to house the collection, the Folgers wanted to give it to the American people. Afraid the price of antiquarian books would soar if their names were revealed, they secretly acquired prime real estate on Capitol Hill near the Library of Congress. They commissioned the design and construction of an elegant building with a reading room, public exhibition hall, and the Elizabethan Theatre. The Folger Shakespeare Library was dedicated on the Bard's birthday, April 23, 1932.